Performance as Transformation: The Laughing Songs of “Death in Venice” in Literature, Film, and Opera (Sound Stage Screen, 2021)
This paper takes as its starting point a scene from the fifth chapter of Thomas Mann’s novella Death in Venice (1912). While Venice is threatened by an outbreak of cholera, a group of Neapolitan street musicians plays in front of Aschenbach, Tadzio, and the other hotel guests. The leader of the band—a buffonesque guitarist-singer with red hair and a wrinkled, emaciated face—is an ominous figure whose facetious, sexually charged performance eventually turns into blatant mockery of the audience, whom he infects with his contagious laughter. Using the concept of “performance as transformation” (Erika Fischer-Lichte) as a lens through which to investigate the filmic and operatic adaptations of the scene in Luchino Visconti’s Death in Venice (1970) and Benjamin Britten’s eponymous opera (1973), I focus on the various renditions of the laughing song to trace the particular transformative power it unfolds across media. Both adaptations use music to ironically comment on Aschenbach’s infatuation. Yet, their approach to the scene at large is distinct from one another: While the opera turns the performance into an interiorized space of moral interrogation, the film evokes the sound of the past through the insertion of pre-existent popular songs from the time, including Berardo Cantalamessa’s Neapolitan laughing song “’A risa.” As I argue, the latter served as a model for the uproarious comical number described by Mann which thus constitutes a “phono-graphic” adaptation itself. Finally, I discuss the recurrences of demonic laughter throughout the film as part of Visconti’s intertextual strategy to create motivic relationships between Death in Venice and Doctor Faustus (1947).
Keywords: adaptation; intermediality; Death in Venice; Visconti; Britten